Circulating growth hormone, cortisol and testosterone in relation to vitamin D status: influence of lower and upper body wingate anaerobic test in elite artistic gymnasts - Mieszkowski, J.; Brzezinska, P.; Kochanowicz, M.; Niespodzinski, B.; Grad, R.; Sawicki, P.; Antosiewicz, J.; Kochanowicz, A. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background and study aim It is well known that professional physical training may be one of the factors modifying s circulating serum level of growth hormone, testosterone and cortisol. However, the effect of high-intensity upper and lower body Wingate Anaerobic Test (WAnT) on the serum hormone levels in association to vitamin D status still remains unspecified. The aim of the current study was to verify hypotheses that a longstanding background in elite gymnastics training induces adaptive changes in hormonal homeostasis during upper- and lower-body WAnT, and that these changes are modulated by muscle group engagement and vitamin D status.